Cost-accuracy and patient experience assessment of blood pressure monitoring methods to diagnose hypertension: A comparative effectiveness study - González-de Paz, Luis; Kostov, Belchin; Freixa, Xavier; Herranz, Carmen; Lagarda, Elena; Ortega, María; Pérez, Elisa; Porcar, Silvia; Sánchez, Eva; Serrato, Montserrat; Vidiella, Ingrid; Sisó-Almirall, Antoni (Frontiers in Medicine, 2022)
Objectives Studies of the diagnosis of hypertension have emphasized long-term cost-effectiveness analysis, but the patient experience and costs of blood pressure monitoring methods at the diagnosis stage remain unclear. We studied four diagnostic methods: a new 1 h-automated office blood pressure (BP) monitoring, office BP measurement, home BP monitoring, and awake-ambulatory BP monitoring. Methods We carried out a comparative effectiveness study of four methods of diagnosing hypertension in 500 participants with a clinical suspicion of hypertension from three primary healthcare (PHC) centers in Barcelona city (Spain). We evaluated the time required and the intrinsic and extrinsic costs of the four methods. The cost-accuracy ratio was calculated and differences between methods were assessed using ANOVA and Tukey’s honestly significant difference (HSD) post-hoc test. Patient experience data were transformed using Rasch analysis and re-scaled from 0 to 10. Results Office BP measurement was the most expensive method (€156.82, 95% CI: 156.18–157.46) and 1 h-automated BP measurement the cheapest (€85.91, 95% CI: 85.59–86.23). 1 h-automated BP measurement had the best cost-accuracy ratio (€ 1.19) and office BP measurement the worst (€ 2.34). Home BP monitoring (8.01, 95% CI: 7.70–8.22), and 1 h-automated BP measurement (7.99, 95% CI: 7.80–8.18) had the greatest patient approval: 66.94% of participants would recommend 1 h-automated BP measurement as the first or second option. Conclusion The relationship between the cost-accuracy ratio and the patient experience suggests physicians could use the new 1 h-automated BP measurement as the first option and awake-ambulatory BP monitoring in complicated cases and cease diagnosing hypertension using office BP measurement.